KARAKTERISTIK DAN ANALISIS TEKS NASKAH “TAFSIR JALĀLAYN 1” KOLEKSI PERPUSTAKAAN MASJID JAMI’ LASEM - Farikha, Dina Nur (STAI AL-ANWAR SARANG, 2021)
This study examines the manuscript copy of the Tafsir Jalālayn 1 from the library collection of the Masjid Jami` Lasem, Rembang district. This research uses both philological and codicological approaches. This research tried to reveal the historical aspects of the manuscript (codicology) and to reveal the characteristics of the text of the manuscript. The historical aspect of this manuscript cannot be revealed because, the researcher failed to find sources from internal manuscripts such as colophons, or other records that can provide clues. There are also no illuminations that can be used as clues to reveal the possible origin of the area where this manuscript was written. However, the identification of the type of paper used in the manuscript gives an early indication that paper was produced at the end of the 17th century. The existence of translation using the interlinear translation (Makna Gandul) and the use of several symbols such as utawi indicate the possibility of this manuscript being copied for learning purposes or even the possibility of further study with evidence there are several notes as comments of Tafsir Jalālayn quoted from several tafsir books such as Anwār al-Tanzīl by al-Baiḍawiy.